Home Visits in Community Supervision: A Qualitative Analysis of Theme and Tone. (October 2017) - Finn, Mary A.; Prevost, John P.; Braucht, George S.; Hawk, Shila; Meredith, Tammy; Johnson, Sharon
Although home visits play a major role in community supervision, little is known about what transpires—what is discussed and with whom the discussion is held. This study addresses that void by qualitatively analyzing case notes of home visits with high-risk parolees who entered supervision in 2008, 2010, or 2012 and exited between 2011 and 2013. Officers' written comments describing 81, 732 home visits were analyzed to uncover discussion themes, tones, and the parties contacted. Of the 12 themes identified, most conversations included parolee contact with the justice system, housing, and employment. Analysis of the tone of comments as neutral, positive, or negative suggested that nearly nine out of 10 notes were neutral containing simple descriptions of the parolee's behavior and status. While home visit interactions were primarily with parolees, parents/grandparents were the second most mentioned participants. Implications for supervision through the lens of therapeutic jurisprudence are discussed.